Discussions On Suitable Modulation Schemes for a Bi-directional Hot Electron Light Emitter and Absorber - Wah, JY; Yenidünya, R; Boland-Thoms, A; Demirer, R. Murat; Balkan, N (IEE-INST ELEC ENG, MICHAEL FARADAY HOUSE SIX HILLS WAY STEVENAGE, HERTFORD SG1 2AY, ENGLAND, 2002)
The hot electron light emitting and lasing semiconductor heterojunction (HELLISH) device is a novel emitter that utilises hot electron/hole transport parallel to the layers of an AlxGa1-xAs p-n junction containing GaAs quantum well(s) in the depletion region. The structure, nicknamed top-hat HELLISH, presented provides a new functionality of the device where n- and p-layers of different lengths are contacted separately but are biased with the same voltage longitudinally. In this configuration carrier injection into the active region is further enhanced in the vicinity of the cathode due to an effective forward biasing as well as the longitudinal biasing of the junction. Therefore, the emission intensity is increased compared with the conventional HELLISH device. Near the anode, however, there is an effective reverse biasing of the junction and in this region the top-hat device acts as an absorber. As a result of these two features, the device can be operated as a wavelength converter or amplifier. The intensity of the emitted light is independent of the polarity of the applied voltage. However, the positions of the absorber and emitter depend on the polarity. Therefore, the device can be operated as a bidirectional wavelength converter and amplifier. The possible modulation scheme and application circuit for this device are discussed.
Keywords: emission; Telecommunications; Optics; Engineering; yayma; Telekomünikasyon; optik; mühendislik